Analyzing uterine rupture: A study from tertiary care centre of western Nepal - Shrestha, Junu; Shrestha, Rami (Journal of Kathmandu Medical College, 2017)
Background: Rupture uterus is a serious obstetric complication which if diagnosed and managed early improves foetomaternal outcome. Objectives: To determine the frequency, causes, management aspects and foeto-maternal outcome of uterine rupture. Methods: This is a cross sectional observational study conducted in Department of Obstetrics and Gynaecology of Manipal Teaching Hospital from July 2012 to June 2015. All cases of rupture uterus, both complete as well as incomplete, diagnosed during surgery were included. Patient’s demographic variables, clinical presentation, risk factors for rupture were studied. Factors related to rupture like the type, nature and site of uterine rupture were noted. The operative management, maternal and neonatal outcome of the patients was reviewed. All the information was entered in the Microsoft Excel chart sheet. Data was analyzed using simple frequencies and percentages. Results: There were 22 cases of uterine rupture and 7987 deliveries during that period giving frequency of 2.8 rupture uterus in every 1000 deliveries. Uterine scar following previous cesarean section was the commonest (72.7%) cause for rupture uterus. Repair was the commonest (86.4%) surgical treatment done. There was no maternal mortality. Blood transfusion was needed two-third of the cases. Other complications were bladder injury (9.1%), paralytic ileus (9.1%), acute renal failure (4.5%) and pneumonia (4.5%). The perinatal mortality was 45.5%. Conclusion: Uterine rupture is a grave obstetric event with maternal and perinatal morbidity and commonly follows pregnancies with scarred uterus.